The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1516-31802011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial laser revascularization versus medical therapy for refractory angina

Abstract: The independent commentary was written by José Henrique Andrade Vila and José Pedro da Silva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…23 There are numerous treatment options aiming at alleviating myocardial ischemia using angiogenic therapeutic approaches (by the so-called myocardial laser revascularization, 24 external shock wave therapy, 25 and myocardial stem cell application 26 ), diastolic coronary pressure augmentation by external counterpulsation, 27 coronary arteriogenesis with induction of large collateral artery remodeling, 28 coronary sinus venous backpressure augmentation, 29,30 and ischemic preconditioning. 31,32 The latter represents the default therapy applied by any primary or secondary prevention program because physical exercise with myocardial ischemia is its cornerstone.…”
Section: Discussionmentioning
confidence: 99%
“…23 There are numerous treatment options aiming at alleviating myocardial ischemia using angiogenic therapeutic approaches (by the so-called myocardial laser revascularization, 24 external shock wave therapy, 25 and myocardial stem cell application 26 ), diastolic coronary pressure augmentation by external counterpulsation, 27 coronary arteriogenesis with induction of large collateral artery remodeling, 28 coronary sinus venous backpressure augmentation, 29,30 and ischemic preconditioning. 31,32 The latter represents the default therapy applied by any primary or secondary prevention program because physical exercise with myocardial ischemia is its cornerstone.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed that transmyocardial [5] and percutaneous myocardial laser revascularization [6, 7], spinal cord stimulation [8] and stem cell therapy [911] may reduce angina symptoms and improve exercise capacity, myocardial perfusion and function. Nevertheless, these treatment modalities are invasive, quite expensive or still at a preclinical stage.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors [8,9,10,11,12] confirm that regional BMC is competent in restoring ischemic myocardium microvasculature and, likely, fix myocardial defects by functioning cardiac myocytes, which leads to a decrease in angina class and partial recovery of cardiac contractility. In this study, we investigated the possibility of BMC to differentiate into cardiomyocytes, with an emphasis on neovascularization in the ischemic myocardium and formation of de novo vessels, without cambial elements of pre-existing vasculature vasculogenesis and prospects for a longterm period.…”
Section: Discussionmentioning
confidence: 99%